1988
DOI: 10.2527/jas1988.66112x
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue, Longissimus Muscle and Anterior Pituitary Growth and Function in Clenbuterol-Fed Heifers

Abstract: The present study was conducted to determine the effects of feeding clenbuterol on adipose tissue and longissimus muscle growth in heifers. For 50 d, 14 heifers were fed either a sucrose-based, clenbuterol supplement or a placebo in which the clenbuterol had been omitted. The heifers were slaughtered in two groups, based on initial weight. Adipose tissue from several anatomical sites and longissimus muscle (depending on slaughter group) were obtained fresh at slaughter. Changes in carcass characteristics elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 12 publications
7
57
0
Order By: Relevance
“…The improvement of the carcass characteristics and the reduction of the weight of organs are in agreement with the findings previously observed in cattle Williams et al, 1987;Miller et al, 1988;Quirke et al, 1988) and sheep (Thornton et al, 1985;Kim et al, 1989). Reductions of the viscera were reported by Williams et al (1987) and Quirke et al (1988).…”
Section: Fortysupporting
confidence: 81%
See 1 more Smart Citation
“…The improvement of the carcass characteristics and the reduction of the weight of organs are in agreement with the findings previously observed in cattle Williams et al, 1987;Miller et al, 1988;Quirke et al, 1988) and sheep (Thornton et al, 1985;Kim et al, 1989). Reductions of the viscera were reported by Williams et al (1987) and Quirke et al (1988).…”
Section: Fortysupporting
confidence: 81%
“…Rumen fermentation characteristics were calculated by analysis of variance in a repeated measures experiment (Snedecor and Cochran, 1980 in Friesian veal calves (Williams et al, 1987) or in crossbred heifers (Miller et al, 1988 (Quirke et al, 1988). Reeds et al (1986) (Stiles et al, 1984).…”
Section: Fortymentioning
confidence: 99%
“…this study increased the mass of the skeletal and cardiac muscle efficiently without altering the body weight, probably due to the concomitant decrease of fat tissue induced by CB through its lipolytic effect (18,19,26). We also performed electrocardiogram (ECG) recording using a telemetric unit (24,25,27).…”
Section: Effects Of Cb On Other Muscles and Heart Ratementioning
confidence: 99%
“…Most studies have demonstrated that BAA increase the cross-sectional area of fast muscle fibers (7)(8)(9) while the results of studies of the effects of BAA on slow muscle fibers have not been consistent. Some studies have demonstrated that the cross-sectional area of slow twitch oxidative fibers is not changed by chronic administration of BAA (8,10,11) while others have shown that all fiber types are affected equally (12,13). Recent reports have established that clenbuterol is able to induce changes in fiber type distribution.…”
Section: Introductionmentioning
confidence: 99%